177 Outpatient letter writing in the neurology department. Issue 6 (27th May 2022) - Lock, Felicity; Wardle, Mark
Abstract : Objective: As a predominantly outpatient-based specialty, neurology clinic letters are a vital, yet often overlooked, communication tool. This study aims to evaluate whether current Neurology outpatient letters in University Hospital of Wales meet the standards suggested by the Academy of Medical Royal Colleges and the Professional Records Standards Body. Methods: An assessment proforma was created based on the standards. A retrospective sample of consult- ant letters from General Neurology, Epilepsy and Multiple Sclerosis outpatient clinics throughout January 2019 were assessed. 2–4 letters were randomly selected from each clinic, aiming for equal numbers of follow-up and new cases. Results: 187 clinic letters were assessed, from 12 different anonymised consultants. Letters universally achieved 'mandatory' PRSB headings, fewer meeting non-mandatory headings. There was a wide variety in style and content, with consultants' mean word counts ranging from 89 to 537. Turnaround delay between clinic and typing ranged from 0 to 79 days, with 79.7% of letters copied to the patient. Conclusion: Though mandatory content was achieved, consistency and clarity often lacked. Present- ing the results at audit meeting prompted much interest and discussion. Many supported implementing a departmental letter structure and exploring reducing turnaround delay to improve the quality and efficiency of outpatient letters. LockFJ@cardiff.ac.uk